2012
DOI: 10.1016/j.virol.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The lectins griffithsin, cyanovirin-N and scytovirin inhibit HIV-1 binding to the DC-SIGN receptor and transfer to CD4+ cells

Abstract: It is generally believed that during the sexual transmission of HIV-1, the glycan-specific DC-SIGN receptor binds the virus and mediates its transfer to CD4+ cells. The lectins griffithsin (GRFT), cyanovirin-N (CV-N) and scytovirin (SVN) inhibit HIV-1 infection by binding to mannose-rich glycans on gp120. We measured the ability of these lectins to inhibit both the HIV-1 binding to DC-SIGN and the DC-SIGN-mediated HIV-1 infection of CD4+ cells. While GRFT, CV-N and SVN were moderately inhibitory to DC-SIGN bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 65 publications
(109 reference statements)
1
50
0
1
Order By: Relevance
“…Indeed, 2 h is enough for HIV endocytosis to reach saturation in permissive cell lines, 12 while 24 h is time enough for replication. 13 And in our study the 5-fold increase of HIV RNA associated with cells from 2 h to 24 h might seem a sign of replication. But virus in the infected cells presumably have not replicated because (1) the B-THP-1/DC-SIGN cell line is almost identical to the Raji/DC-SIGN 14 and (2) endocytosis of HIV in Raji/DC-SIGN cells is not observed and they are not permissive to HIV infection.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Indeed, 2 h is enough for HIV endocytosis to reach saturation in permissive cell lines, 12 while 24 h is time enough for replication. 13 And in our study the 5-fold increase of HIV RNA associated with cells from 2 h to 24 h might seem a sign of replication. But virus in the infected cells presumably have not replicated because (1) the B-THP-1/DC-SIGN cell line is almost identical to the Raji/DC-SIGN 14 and (2) endocytosis of HIV in Raji/DC-SIGN cells is not observed and they are not permissive to HIV infection.…”
supporting
confidence: 49%
“…12 Inhibitors of HIV infection and transinfection via the DC-SIGN lectin receptor have been tested only in preclinical studies. [13][14][15] Development or application of known drugs for the inhibition of HIV/DC-SIGN interaction may help in decreasing transinfection of T cells and in preventing the infection of DCs that serve as a long-term reservoir of HIV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although DENV has high mannose-type glycans on the E-protein, there was no antiviral activity of AH against DENV infection. Other CBAs such as microvirin, griffithsin and Banlec have been shown to exhibit potent activity against HIV replication [93][94][95], but these CBAs did not show antiviral activity against DENV. Previously, it has been shown that the CBAs HHA, GNA and UDA also target the N-glycans of other viruses, such as HIV, HCV [79] and HCMV [80].…”
Section: Broad Antiviral Activity Of Cbas Against Denvmentioning
confidence: 99%
“…and spleens (C) weights were measured relatively to body weight at sacrifice. [29,31,37,142,189,190].…”
Section: Discussionmentioning
confidence: 99%